Trypanosome parasites in four species of ranid frogs from Peninsular Malaysia - Miyata, Akira; Yong, H. S. (Malaysian Journal of Science, 1994)
Four species of ranid frogs - Rana cancrivora, Rana erythraea, Rana hosei and Rana limnocharis - from several localities in Peninsular Malaysia were examined for trypanosome infection. Rana hosei is a forest frog, while R. cancrivora, R. erythraea and R. limnocharis are commensal species. All of them were infected with a variety of trypanosomes. The prevalence and type of infection (with single or mixed trypanosome-type) differed from locality to locality. Parasites of Trypanosoma chattoni group and Trypanosoma rotatorium group were present in all the four species of frogs. The next common group of parasites belonged to Trypanosoma bocagei-type which were found in R. erythraea, R. limnocharis and R. hosei. Trypanosomes of Trypanosoma loricatuna-type were found in R. erythraea and R. hosei, Trypanosoma tsukamotoi-type in R. erythraea and R. limnocharis, Trypanosoma hosei in R. hosei and Trypanosoma mega-type in R. limnocharis. Of these parasites, T. raksasa the T. loricatum-type found in R. erythraea, is perhaps the largest trypanosome of anuran origin in the world. Trypanosoma hosei is unique, being very similar morphologically to the trypanosomes known from freshwater fishes.